AB0124 Inhibitory Effects of A Novel Bispecific Antibody against Tnf-Alpha and CXCL10 in Animal Model of Rheumatoid Arthritis. (10th June 2014) - Yoo, H.J.; Park, S.H.; Kim, S.Y.; Kang, S.E.; Song, J.E.; Shin, K.; Lee, E.Y.; Lee, E.B.; Park, Y.W.; Kang, H.S.; Song, Y.W.
Abstract : Background: Tumor necrosis factor-α (TNF-α) plays a crucial role in the pathogenesis of rheumatoid arthritis (RA) and monoclonal antibodies targeting TNF-α are used as a popular therapeutic interventions in RA patients. CXCL10 is a chemokine that potentially plays a role in the immunopathogenesis of RA. The development of bispecific antibody (BiAb) as a therapeutic agent for RA may have great clinical potential. We constructed a single-chain BiAb against both TNF-α and CXCL10 (IgG-based format). Objectives: We investigated the inhibitory effects of BiAb targeting TNF-α and CXCL10 on in vitro and in vivo model of RA. Methods: We performed TNF-α neutralization assay using WEHI cell and tube formation assay of HUVEC cell to investigate TNF-α antagonistic effect of BiAb. Then we performed T cell migration assay induced by CXCL10 using transwell system and inhibitory assay of osteoclastogenesis. The effects of BiAb were determined by arthritis severity score, histological damage in Tg197 human TNF transgenic mice. Results: BiAb suppressed TNF-α comparatively with adalimumab in TNF-α neutralization assay, tube formation assay and osteoclast differentiation. Cell migration induced by CXCL10 was inhibited by BiAb dose dependently. Treatment with BiAb resulted in beneficial effects on clinical and histological parameters of Tg197 human TNF transgenic mice model. Conclusions: Our results demonstrate the novel BiAb effectively neutralized TNF-α and CXCL10 in vitro and in vivo model of rheumatoid arthritis. We suggest that BiAb could be a promising biologic agent for the treatment of RA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3074